Construction of environment-friendly core-shell ammonium perchlorate@1, 3, 5-triamino-2, 4, 6-trinitrobenzene composites with high safety and excellent thermal decomposition properties. (June 2020) - Ye, Ping; Xu, Pengfei; Guo, Hao; Gao, Bing; Yang, Guangcheng; Huang, Bing; Guo, Changping
Abstract: Modern solid propellants integrated with enviro-friendly, high safety and excellent thermal decomposition properties are highly desired in the aerospace as well as weapon areas, and it also presents significant challenging. For this purpose, a simple ultrasonic synthesis method was proposed to 1, 3, 5-triamino-2, 4, 6-trinitrobenzene (TATB) nanoparticles were deposited on the surface of ammonium perchlorate (AP) to obtain core-shell AP@TATB. Since there is no heavy metal involved in the composite, it can effectively avoid the pollution of heavy metals to the environment. The prepared samples were analyzed by powder X-ray diffraction (XRD), scanning electron microscopy (SEM) and X-ray photoelectron spectroscopy (XPS), it has been confirmed that a uniform and complete shell TATB was formed on the surface of AP particles when the content of TATB was 10%, differential scanning calorimetry (DSC) data shows that the shell TATB effectively reduces the high-temperature decomposition (HTD) of AP and significantly increases heat release of AP by 2.67 times. In addition, AP@TATB also showed excellent safety in the sensitivity test. The ease of the synthesis method and the promising feature of the obtained composites exhibit great potential for application in environment-friendly modern solid propellants. Graphical abstract: Unlabelled Image Highlights: The core-shell structure is designed by simple and mild ultrasonic synthesis. TATB is enviro-friendly as the catalyst, compared to transition metal oxides. Perfect safety is based on the characteristics of TATB and the core-shell structure. Excellent thermal decomposition performance is caused by synergistic effect.